Personalised analytics for rare disease diagnostics - Denise Anderson (Nature Portfolio, 2019)
Genome sequencing is being widely adopted for diagnosis of genetic diseases, but identifying the causal variants remains challenging. Here, the authors introduce a tool that incorporates tissue-specific gene expression data into predicting variant pathogenicity, improving accuracy.